The effectiveness of health promotion (audiovisual and leaflet) on adolescents' behavior regarding breast self-examination - Abni, Elmy Novia; Kasim, Ahmad Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: Breast cancer is a leading cause of mortality among women worldwide. Early Breast Self-Examination (BSE) detection can be crucial in reducing late-stage diagnosis and improving survival rates. This study aims to evaluate the effectiveness of audiovisual media and leaflet-based health promotion on adolescents' knowledge, attitudes, and practices regarding breast self-examination. Research Methodology: This type of research is quantitative. The design used is the pre-test-posttest control group design, which is considered relevant to the assessment of health education or training initiatives. The sampling method used is random sampling. The paired t-test was used for data analysis, and the independent t-test was used to compare the variation in knowledge scores between the two treatments. Result: Paired tests showed that the average knowledge score of the V2 group was higher than that of the V1 group (20.934 vs. 10.208) in the pre-test to post-test-1, with a significant increase in knowledge (p<0.05) between the two groups. Similarly, the average knowledge score of the V2 group was higher than that of the V1 group (19.646 vs. 7.183) in the pre-test to post-test-2, and their attitude change was more significant than that of the V1 group (7.980 vs. 2.765). However, in the pre-test to post-test-1, the attitude change between the V1 and V2 groups was insignificant (p>0.05). Likewise, the average attitude change score of the V2 group in the pre-test to post-test-2 was higher than that of the V1 group (6.555 vs. 2.009), although the difference was not statistically significant (p>0.05). Conclusion: This study concludes that the leaflet approach to adolescents' behavior regarding breast self-examination (BSE) substantially impacts improving knowledge and attitudes about the effectiveness of health promotion before and after its implementation.